Nutritional problems of liver transplant candidates - Sökülmez Kaya, Pınar; Eba Demirbağ, Ali; Akdoğan Kayhan, Meral (Progress in Nutrition, 2016)
Aim: The study aims to evaluate the nutritional problems of the patients on the waiting list for liver transplantation due to the high risk. Methods: The study evaluates the nutritional status of 102 liver transplant candidates including 41 women and 61 men followed by the liver transplantation team of the Hospital in Ankara. Data collected was evaluated using SPSS 21.0 statistical software. Continuous variables were expressed as mean ± SD and categorical variables as percentages. Results: The average weight of the patients on the list of liver transplant candidates was 78.5±15.5 kg. According to BMI, 37.6% of the patients were found to be overweight and 37.6% were obese; and according to SGA, 28.4% of the patients (29 persons) were found to have moderate PEM. 76.5% of the patients skip meals; and 53.9 skip meals because they do not want to eat. 12.7% do not eat at all and 41.2% eat less than usual when they are sad or tired. 75.5% eat salty/less salty foods. 46.1% received training in diet and 48% follow their diet plans. Conclusion: Obesity may also threaten all patients with chronic liver disease as much as malnutrition. Thus, as one of the variables affecting the morbidity and mortality in patients on the waiting list for liver transplantation, nutritional status should be well followed up and necessary changes should be made.